2011
DOI: 10.1002/glia.21235
|View full text |Cite
|
Sign up to set email alerts
|

Microglial zinc uptake via zinc transporters induces ATP release and the activation of microglia

Abstract: Previously, we demonstrated that extracellular zinc plays a key role in transient global ischemia-induced microglial activation through sequential activation of NADPH oxidase and poly(ADP-ribose) polymerase (PARP)-1. However, it remains unclear how zinc causes the sequential activation of microglia. Here, we examined whether transporter-mediated zinc uptake is necessary for microglial activation. Administration of zinc to microglia activated them through reactive oxygen species (ROS) generation and poly(ADP-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 80 publications
1
51
0
Order By: Relevance
“…Ionotropic P2X and metabotropic P2Y ATP receptors and P1 adenosine receptors have been detected on microglia (39, 82, 109,111,159,167,176,201,289,292,293,371,394,415,442). A series of experiments have demonstrated that ATP and its analogs trigger a rather rapid change of microglia into an activated phenotype (82, 110,164,173). The role of purinergic receptors in regulating physiological responses in surveilling microglia is poorly understood.…”
Section: B Microglia Express Neurotransmitter Receptorsmentioning
confidence: 97%
“…Ionotropic P2X and metabotropic P2Y ATP receptors and P1 adenosine receptors have been detected on microglia (39, 82, 109,111,159,167,176,201,289,292,293,371,394,415,442). A series of experiments have demonstrated that ATP and its analogs trigger a rather rapid change of microglia into an activated phenotype (82, 110,164,173). The role of purinergic receptors in regulating physiological responses in surveilling microglia is poorly understood.…”
Section: B Microglia Express Neurotransmitter Receptorsmentioning
confidence: 97%
“…[44][45][46][47] In this study, exposure of HEK293T/ hP2X7R and HEK293T/mP2X7R cells to DMCs decreased, but not increased, their YP uptake dose-dependently, denying decrease of their viability under our experimental condition. As for pannexin-1, Bhaskaracharya et al reported that neither carbenoxolone (up to 100 µM) nor 10 Panx peptide (100 µM), both of which are a pannexin-1 blocker, had any effects on ATP-induced uptake of ethidium, a pannexin-1-permeable dye, by hP2X7R-expressing HEK293 cells, 48) and Browne et al demonstrated that P2X7R channels allow direct permeation of nanometer-sized dyes including YP and ethidium in rP2X7R-expressing HEK293 cells. 49) Taken together, we consider that inhibitory effects of DMCs on BzATP/ATP-evoked YP uptake by HEK293T/hP2X7R and HEK293T/mP2X7R cells reflect the inhibition of agonist-evoked P2X7R activation, but not pannexin-1, in the cells.…”
Section: Discussionmentioning
confidence: 99%
“…4,5) Of P2XRs, P2X7R has unique characteristics, and its affinity for ATP is extremely low and its prolonged activation leads to formation of channels/pores. 6,7) In neuronal cells, extensive activation of P2X7Rs causes the death of neurons, 8,9) and induces microglial activation 10) and astrocytic engulfing activity. 11,12) In immune cells, ATP-induced P2X7R activation triggers Nod-like receptor family, pyrin domain containing 3 (NLRP3) inflammasome activation, followed by generation/ release of inflammatory cytokines.…”
mentioning
confidence: 99%
“…In addition to differences in astrocytic P2X7R functionality between ddY-and SJL mice, 13) very recently, we found that cultured neurons derived from ddY-strain mouse cortices exhibit lower ATP sensitivity than those from SJL-strain ones (data not shown). As for microglia as immune cells in the CNS, ATP can induce their chemotaxis via P2X7R activation, 3) while astrocytic engulfing activity, which involves in an innate immune response, was regulated by P2X7Rs under non-stimulated resting conditions. 14) On the other hand, alteration of P2X7R-related channel/pore activity caused by single nucleotide polymorphisms of the P2rx7 gene is reported to be associated with human psychiatric diseases such as affective mood disorders.…”
Section: Discussionmentioning
confidence: 99%
“…These responses help keep the brain environment clean, while under severe pathological conditions, neuronal injury is exacerbated. [1][2][3][4][5][6][7][8] Astrocytes, a major cell population in the brain, also express a P2X7R, and its activation leads to the release of glio-transmitters, such as glutamate, 9) ATP, 10) and zinc, 3,11) which are considered to play critical roles in the neuron-glia network system in the central nervous system (CNS), but the details have not been fully clarified.…”
mentioning
confidence: 99%